Quantum machine learning for image classification - Myat Kaung (Nanyang Technological University, 2022)
Quantum Machine learning is a promising technology that is related to the study of computing. Due to the property of quantum systems, it has become an area of research that is focused on solving computational problems using quantum parallelism, which can give computational advantages such as faster computational speed, reducing time considerations for classical computing tasks to achieve. By comparison, in classical conventional computation, it can have only two states: if it is ON, it is ‘1’ and if it is OFF, it is ‘0’. Using all the modern computational devices for instance, laptops, computers, and mobile phones use these two simple digits. On the other hand, in quantum computing, there is a special feature called superposition, which allows a quantum bit to be at both ‘0’ and ‘1’ state at the same time. This superposition can be used in parallel processing tasks for example, big data, Machine learning, etc.